Low-dimensional magnetism of spin-½ chain systems α- and β-TeVO4: a comparative study: Оптика и магнитооптика - Gnezdilov, V.; Lemmens, P.; Wulferding, D.; Pashkevich, Yu.; Lamonova, K.; Choi, K.-Y.; Afanasiev, O.; Gnatchenko, S.; Berger, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We present a comparative study of the low-dimensional compounds α- and β-TeVO4. Our data clearly showthat the change in the local coordination geometry of V4+ ions comparing α- and β-TeVO4 leads to a drastic differencesin the magnetic properties. Despite sharing the same crystal structure, the two compounds realize different magnetic exchange topologies. Both compounds exhibit a transition from ferro- to antiferromagnetic correlationswith decreasing temperature. This effect however is driven by different mechanisms for both compounds.Additionally, a dimensional crossover is found in β-TeVO4.